Generating Micro, Small and Medium Enterprises in a Pandemic Period with Innovation and Technology - Hamdani; Eneng Wiliana; Nining Purnaningsih; Dhea Zatira; Khorida AR (MOVE: Journal of Community Service and Engagement, 2022)
The seminar "Generating MSMEs in a Pandemic Period with Innovation and Technology" is an activity to provide knowledge and an overview of how to survive and even develop a business during and after the occurrence of COVID-19 which caused the economy to decline, in order to maintain and improve people's welfare. The purpose of the implementation of this activity is to awaken MSMEs to be able to compete during the pandemic so that businesses can continue to run, MSMEs are able to compete with Competitors during a pandemic by utilizing technology, Increasing creativity by innovating, Being able to improve social media for promotional facilities. , Able to Improve the Ability of MSMEs in terms of financial management, MSMEs better understand the Financial Processing system and MSMEs better understand how the process of capital financing